Cigarette smoke-induced oxidative stress activates NRF2 to mediate fibronectin disorganization in vascular formation - Jinjiang Xue (Open Biology, 2022)
Cigarette smoke significantly induces oxidative stress, resulting in cardiovascular disease. NRF2, a well-known antioxidative stress response factor, is generally considered to play protective roles in cardiovascular dysfunction triggered by oxidative stress. Interestingly, recent studies reported adverse effects of NRF2 on the cardiovascular system. These unfavourable pathogenic effects of NRF2 need to be further investigated. Our work shows that cigarette smoke extract (CSE)-induced oxidative stress disturbs fibronectin (FN) assembly during angiogenesis. Furthermore, this effect largely depends on hyperactive NRF2-STAT3 signalling, which consequently promotes abnormal FN deposition. Consistently, disruption of this pathway by inhibiting NRF2 or STAT3 prevents CSE-induced FN disorganization and vasculature disruption in human umbilical vein endothelial cells or zebrafish. Taken together, these findings demonstrate the cardiovascular dysfunction caused by CSE from a novel perspective that NRF2-dependent signalling engages in FN disorganization.